Energy consumption profiles of wireless sensor nodes in smart cities using CupCarbon (V 5.0) simulator. (25th August 2022) - Prabhakar, Hanshita; Furqan, Asna
In the development of smart cities, smart devices are integrated with sensors and embedded systems to provide innovative services which enhance the internet of things (IoT); also, the power consumed by these devices for specific operations will be a primary concern. Wireless sensor network (WSN) consists of enormous numbers of sensor nodes densely deployed over smart city sensor nodes that are efficient in collaborating and computing the condition of their surrounding environments. The proposed work of this paper is analysing how the different profiles of wireless sensor networks for intelligent cities consume energy as routing, communication of messages between two sensors, broadcasting of transmissions, and mobility is shown by the graph of energy consumption in joule (J) versus simulation time in seconds (S). We have performed and analysed the results on the network simulator called CupCarbon simulator. The novelty of this paper is that we could examine and estimate the errors while the transmission and reception happen in between the sensor nodes with the help of the console output messages.